The Effect of Capital Adequacy, Credit Risk, and Liquidity on Commercial Banks Profitability in Indonesia Stock Exchange - Anastasia Anggraini; Dewa Gede Dharma Suputra (Penerbit Kemala Indonesia, 2021)
The purpose of this study was to analyse the effect of capital adequacy, credit risk, and liquidity on company profitability. The research population is all banking companies listed on the Indonesia Stock Exchange (BEI). The sampling technique used purposive sampling method, namely the method of determining the sample with certain considerations. The sample criteria are the banking sector that is listed continuously on the Indonesian Stock Exchange as many as 38 banking companies listed on the IDX continuously during the 2015 - 2019 period. The results show that capital adequacy and liquidity have a positive effect on profitability and credit risk have a negative effect on profitability. This study illustrates that capital adequacy, liquidity, and credit risks can predict the level of profitability that can be used by investors and stakeholders in taking decisions.